Neuroteaching Based on Islamic Education to Manage Good Learning - Muzdalifah, Muzdalifah; Isnawati, Zakiyah (QUALITY, 2024)
Teachers’ teaching skills are an important factor in achieving learning success. However, almost 75% of teachers do not prepare the learning process well. Neuroteaching can be used as an effort to improve teaching skills because Neuroteaching is a teaching method that can hone participants’ cognitive, emotive, and psychomotor skills. This study aims to explore in-depth data on the implementation of the concept of Neuroteaching based on Islamic education as an alternative guideline for teaching skills for alumni of the Faculty of Education IAIN Kudus and the inhibiting, supporting, and solution factors. This study uses a qualitative method with a case study approach. The results showed that respondents as alumni of the Tarbiyah Faculty of IAIN Kudus scored high in teaching skills are 420-528. Inhibiting factors for the implementation of Neuroteaching include limited access to references, time and resources, difficulties in large classes, inadequate technology, resistance to change, limitations of the school environment, lack of support and training, and pressure from performance evaluations. The supporting factors include; professional training, resources and technology, school leadership support, personalization of learning, support from parents and the community, and perceptions about the importance of Neuroteaching. Efforts to facilitate the implementation of Neuroteaching are to improve the management of Islamic education in TK-SD Al-Maun Jepara which includes the role of the principal, training for teachers, adequate facilities and infrastructure, cooperation between parents and the community, and appreciation for teacher achievement.